Comparison of uphill sprint training to cycle sprint training - Jakeman, J. R.; Lorimer, R.; Babraj, J. A. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
High intensity training (HIT) involving 30sec sprints is an effective approach to improving aerobic performance. However much of this research is based on cycle ergometry, with access to equipment difficult, and the protocol non sport-specific. We investigated whether 30sec uphill running sprints could deliver similar improvements in aerobic performance as cycle HIT and the similarity of metabolic demand. Methods: Eleven recreationally active males (35 ± 8 y, weight 82 ± 10 kg, BMI 26 ± 3 kg/m^2) were recruited and allocated to either a cycle training group (CT n=5) performing two weeks of HIT, or a run training group (RT n=6) performing 2 weeks of uphill sprints on a 1:10 slope. The sprint intervention for both groups involved 4 x 30 sec sprints separated by 4 min active recovery, 3 x per week (totalling 6 sessions, with a total exercise time of 12 min). Before and after 2 weeks of training participants performed a VO2 max and time to exhaustion (TTE) test on a cycle or treadmill ergometer, with protocols seeking to produce similar TTE. On separate occasions 6 participants performed 2 uphill or cycle sprints with portable breath by breath analysis and blood lactate taken 1 minute after each sprint. Results: Two weeks of HIT resulted in an 11% increase in TTE in the RT group and a 6% increase in TTE in the CT group (p = 0.014 and p=0.05 respectively). The improvement in TTE was associated with an increase in the % VO2 max where VCO2 excess occurred (RT- pre 66 ± 10%, post 78 ± 5%; p<0.01 pre versus post: CT- pre 53 ± 2%, post 64 ± 4%; p<0.05 pre versus post). Further, blood lactate was significantly lower after the first uphill sprint compared to the first cycle sprint (5.1 ± 2.4 versus 10.2 ± 1.3 mmol/l, p<0.001). However blood lactate levels were similar after the second sprint (12.5 ± 2.2 versus 14.1 ± 1.7 mmol/l, NS). The first uphill sprint produced a greater area under the curve for heart rate, VO2 and VCO2 than the cycle sprint during the sprint and 4 minute recovery (p<0.05 for all). However, only area under the curve for VO2 was greater for uphill sprinting compared to cycle for the second sprint (p<0.05). Discussion: In the present study we demonstrate that uphill sprints can improve aerobic performance to a similar extent as a cycle HIT protocol. The magnitude of change in VCO2 excess is similar following RT and CT suggesting both protocols produce similar adaptations in lactate metabolism. There is a greater oxygen demand in the first uphill sprint which results in a lower blood lactate concentration suggesting a higher aerobic contribution to an uphill sprint compared to a cycle sprint. In conclusion uphill sprints are as effective as traditional cycle high intensity training to improve aerobic performance in recreationally active males.